2021
DOI: 10.1111/adj.12826
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of low‐molecular weight chitosan against Candida albicans biofilm on polymethyl methacrylate resin

Abstract: Background Candida biofilm is a major cause of denture stomatitis. We aimed to compare the efficacy of low‐molecular‐weight chitosan solutions against Candida albicans biofilm on polymethyl methacrylate (PMMA) resin. Methods Various types of chitosan were tested for anti‐Candida activity by broth dilution. Two types were selected for further testing on 24‐hour C.albicans biofilm formed on PMMA specimens. Specimens were randomly distributed among experimental groups, including 0.1% and 0.2% acetic acid, 3 and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…It is advantageous to administer a combination of antifungal agent and antimicrobial photodynamic therapy in the management of infection related to Candida biofilm 30,31 . Moreover, low‐molecular‐weight chitosan solution was found as an effective antifungal denture cleanser that can significantly reduce C. albicans viability in biofilms on polymethyl methacrylate resin used for fabrication of acrylic dentures 32 …”
Section: Discussionmentioning
confidence: 99%
“…It is advantageous to administer a combination of antifungal agent and antimicrobial photodynamic therapy in the management of infection related to Candida biofilm 30,31 . Moreover, low‐molecular‐weight chitosan solution was found as an effective antifungal denture cleanser that can significantly reduce C. albicans viability in biofilms on polymethyl methacrylate resin used for fabrication of acrylic dentures 32 …”
Section: Discussionmentioning
confidence: 99%
“…However, it needed a long contact time of over 10 min, so it is likely more effective when applied as a root-canal medication rather than as an irrigant. In addition, we also showed that these chitosan derivatives has a minimum fungicidal concentration against C. albicans at 4 mg/ml (17). Thus, in this study, we formulated 4 mg/ml of 1700 KDa chitosan in 0.2% acetic acid into a paste for application as an antimicrobial intracanal medication.…”
Section: Discussionmentioning
confidence: 88%
“…However, it needed a long contact time of over 10 min, so it is likely more effective when applied as a root-canal medication rather than as an irrigant. In addition, we also showed that these chitosan derivatives has a minimum fungicidal concentration against C. albicans at 4 mg/ml [ 16 ]. Thus, in this study, we formulated 4 mg/ml of 1700 KDa chitosan in 0.2% acetic acid into a paste for application as an antimicrobial intracanal medication.…”
Section: Discussionmentioning
confidence: 99%